Multi-level change strategies for health: learning from people-centered advocacy in Uganda - Angela Bailey; Vincent Mujune (BMC, 2022)
Abstract Background The paper analyzes how the Accountability Can Transform Health (ACT Health) program activated bottom-up citizen action to secure government responses and more accountable health services in Uganda. The ACT Health program had two phases-Phase 1 focused on a community-level intervention studied with a randomized control trial, and Phase 2 supported citizen-led advocacy targeting government officials across multiple levels. The focus of this paper is an analysis of Phase 2, when the "people-centered advocacy" approach supported almost 400 community advocates representing 98 health facilities to organize, identify joint advocacy priorities, directly monitor health services, and collaborate on health advocacy campaigns in 18 districts. Most district campaigns focused on the complex, power-laden issue of health worker absenteeism. With a few notable exceptions, iterative cycles of engagement between citizens and the state across multiple levels are infrequently discussed in the formal literature on health accountability. Methods This paper is based on a comparative, inductive, practitioner-led analysis of program monitoring data from 18 multi-level health advocacy campaigns. The findings emerge from analysis of a "Heat Map," capturing grounded accounts of government responses to community-led advocacy. Results Officials in eight out of 18 districts fulfilled or surpassed commitments made to community advocates. Government responses included: increased monitoring, more downward accountability, countering backlash against advocates, applying sanctions for absent health workers, and increased budget allocations. Advocates' bottom-up advocacy worked in part through triggering top-down responses and activating governmental checks and balances. Conclusions Methodologically, this article demonstrates the value of analyzing process monitoring and program data to understand outcomes from direct engagement between citizens and the state to improve health services. Survey-based research methods and quantitative analysis may fail to capture signs of government responsiveness and relational outcomes (such as subtle signs of shifting power dynamics) many hope to see from citizen-led accountability efforts. Practitioners' perspectives on how accountability for health emerges in practice are important correctives to much positivist research on accountability, which has a tendency to ignore the complex dynamics and processes of building citizen power.